2016
DOI: 10.17310/ntj.2016.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tax Disclosures and Corporate Tax Avoidance

Abstract: This paper examines whether three recent mandatory tax disclosure regimes (Schedule M-3, FIN 48, and Schedule UTP) are associated with long-term changes in corporate tax avoidance. We find that both the Schedule M-3 and Schedule UTP disclosure regimes are associated with increased levels of tax avoidance while the FIN 48 disclosure regime is associated with decreased levels of tax avoidance. We also posit that these associations could differ for domestic and multinational firms because of the specific informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
1
27
0
3
Order By: Relevance
“…The implementation of Schedule UTP requires consistency by a firm in the reporting of UTPs across financial statements and tax filings lodged with the IRS. Research by Henry, Massel, & Towery () finds that Schedule UTP disclosure requirements are associated with higher levels of corporate tax avoidance. These results are consistent with the idea that a firm's UTP reporting requirements may provide information about its tax avoidance activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of Schedule UTP requires consistency by a firm in the reporting of UTPs across financial statements and tax filings lodged with the IRS. Research by Henry, Massel, & Towery () finds that Schedule UTP disclosure requirements are associated with higher levels of corporate tax avoidance. These results are consistent with the idea that a firm's UTP reporting requirements may provide information about its tax avoidance activities.…”
Section: Resultsmentioning
confidence: 99%
“…As additional analysis, we also consider the impact of UTP reporting requirements on the association between income-shifting arrange- Henry, Massel, & Towery (2016) finds that Schedule UTP disclosure requirements are associated with higher levels of corporate tax avoidance. These results are consistent with the idea that a firm's UTP reporting requirements may provide information about its tax avoidance activities.…”
Section: Additional Analysis: the Impact Of Uncertain Tax Position mentioning
confidence: 99%
“…In response to this threat, firms' tax disclosure strategies are varied; in some cases even, no response is provided. Henry et al (2016) recently observed that disclosure requirements providing relevant information about tax avoidance activities are associated with lower levels of tax avoidance. Taking the relationship the other way round, Gleason and Mills (2002) provide evidence that managers of companies using tax planning are unwilling to disclose information about these activities.…”
Section: Related Literaturementioning
confidence: 99%
“…Aqui, identificam-se tanto investigações teóricas (De Simone, Sansing & Seidman, 2013) como empíricas (Bozanic, Hoopes, Thornock & Williams, 2017). As pesquisas centram-se, predominantemente, no papel das autoridades fiscais na inibição da Agressividade Tributária (Hoopes, Mescall & Pittman, 2012), a distância à autoridade fiscal da sede física do sujeito passivo (Kubick, Lockhart, Mills & Robinson, 2017), a atuação dos reguladores financeiros, tais como o monitoramento da SEC, (Hope, Ma & Thomas, 2013; e o papel da transparência fiscal (Beck & Lisowsky, 2014;Henry, Massel & Towery, 2016).…”
Section: Restrições Dos Gatekeepersunclassified